IMPLEMENTASI SMART POWER DAN LINKAGE ISSUES INDONESIA DALAM PERLINDUNGAN KEDAULATAN MARITIM DI KEPULAUAN NATUNA - Muhammad Ridha Iswardhana; Puguh Toko Arisanto (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2022)
The study will discuss the protection of Indonesia's maritime sovereignty in Natuna using the theory of smart power, linkage issues, and national security. First, smart power explains the use of power; the Indonesian government intelligently combines various decisions and resources to gain China's legitimacy regarding national interests in Natuna. Second, the Linkage Issues theory identifies the use of policies outside the defence sector that impact China. Third, national security explains various efforts to protect Indonesia's sovereignty in various fields, such as trade and politics. The research method is qualitative explanatory as a case study analysis to explain Indonesia's strategy to protect the sovereign territory in Natuna. This research shows Indonesia as a great country with a higher bargaining position that tries to protect its sovereign territory. The article proves that Indonesia has a strong bargaining position in protecting the Natuna region by using various strategic policies that impact China, even though China is more assertive in the political and military aspects.